Efficacy and safety of platelet-rich plasma injections for the treatment of osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Xiong, Yongqing; Gong, Cheng; Peng, Xumiao; Liu, Xianlei; Su, Xinda; Tao, Xi; Li, Ying; Wen, Youliang; Li, Wei (Frontiers in Medicine, 2023)
Background In recent years, platelet-rich plasma (PRP) injections for osteoarthritis (OA) have been widely promoted in clinical practice, but their effectiveness is controversial. Therefore, we conducted a meta-analysis of relevant randomized controlled trials (RCTs) to determine the efficacy and safety of PRP injections for the treatment of OA. Methods We searched databases including Embase, Web of Science, Medline, PubMed, and the Cochrane Library for relevant studies. Two researchers (YQX and CG) performed literature screening, baseline data extraction, literature quality assessment, and heterogeneity analysis of RCTs from the retrieved studies. Based on the magnitude of heterogeneity I2, random-effects or fixed-effects models were selected for the meta-analysis. Results We included 24 RCTs comprising 1344 patients with OA who met the inclusion criteria, with the main types of morbidity being knee osteoarthritis (KOA), hip osteoarthritis (HOA), ankle osteoarthritis (AOA), and temporomandibular joint osteoarthritis (TMJOA). Our results indicate that PRP injections were effective in improving Visual Analog Scale (VAS) pain scores in patients with KOA, HOA, and AOA compared to controls (AOA, MD = −1.15, CI = 95% [−1.74, −0.56], I2 = 40%, P < 0.05; KOA, MD = −1.03, CI = 95% [−1.16, −0.9], I2 = 87%, P < 0.05; TMJOA, MD = −1.35, CI = 95% [−1.74, −0.97], I2 = 92%, P < 0.05) but showed no significant efficacy in patients with HOA (MD = −0.27, CI = 95% [−0.8, 0.26], I2 = 56%, P>0.05). Compared to controls, PRP injections were effective in improving Knee Injury and Osteoarthritis Outcome Score (KOOS), including the patient's pain symptoms, activities of daily living (ADL), and adhesion symptomatology, but not for that of sports function (KOOS-pain, MD = 2.77, CI = 95% [0, 5.53], I2 = 0%, P < 0.05; KOOS-symptoms, MD = 3.73, CI = 95% [0.76, 6.71], I2 = 0%, P < 0.05; KOOS-ADL, MD = 3.61, CI = 95% [0.79, 6.43], I2 = 0%, P < 0.05; KOOS-QOL, MD = 4.66, CI = 95% [0.98, 8.35], I2 = 29%, P < 0.05, KOOS-sport, MD = 0.48, CI = 95% [−3.02, 3.98], I2 = 0%, P > 0.05). PRP injections were effective in improving Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores, including pain, stiffness, and functional joint motion, in patients with OA compared with the control group (WOMAC-pain, MD = −1.08, CI = 95% [−1.62, −0.53], I2 = 87%, P < 0.05; WOMAC-stiffness, MD = −1.17, CI = 88% [−1.72, −0.63], I2 = 87%, P < 0.05; WOMAC-function, MD = −1.12, CI = 95% [−1.65, −0.58], I2 = 87%, P < 0.05). In addition, subgroup analysis showed that leukocyte-poor (LP) PRP injections were more effective than leukocyte-rich (LR) PRP injections in improving pain symptoms in patients with OA (VAS, LR-PRP, MD = −0.81, CI = 95% [−1.65, −0.03], I2 = 83%, P = 0.06 > 0.05; LP-PRP, MD = −1.62, CI = 95% [−2.36, −0.88], I2 = 92%, P < 0.05). A subgroup analysis based on injection sites showed that no statistical difference in efficacy between intra-articular (IA) combined with intra-osseous (IO) simultaneous PRP injections. IA PRP injections only improved VAS pain scores in patients with OA (IA+IO PRP injections, MD = −0.74, CI =95% [−1.29, −0.18], I2 = 61%, P < 0.05; IA PRP injections, MD = −1.43, CI = 95% [−2.18, −0.68], I2 = 87%, P < 0.05, test for subgroup differences, P > 0.05, I2 = 52.7%). Conclusion PRP injection therapy can safely and effectively improve functional activity in patients with OA and produce positive analgesic effects in patients with KOA, TMJOA, and AOA. However, PRP injection therapy did not significantly reduce pain symptoms in patients with HOA. In addition, the analgesic effect of LP-PRP was greater than that of LR-PRP. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022362066.